Temperature-dependent luminescence of europium-doped Ga₂O₃ ceramics - Kumarbekov, Kuat K.; Kakimov, Askhat B.; Karipbayev, Zhakyp T.; Kassymzhanov, Murat T.; Brik, Mikhail G.; Ma, Chong-geng; Piasecki, Michał; Suchikova, Yana; Kemere, Meldra; Konuhova, Marina (Elsevier B.V., 2025)
This study explores the synthesis and luminescent properties of europium-doped gallium oxide (Ga₂O₃:Eu) ceramics fabricated via electron beam-assisted synthesis (EBAS) at 1.4 MeV. The resulting Ga₂O₃:Eu ceramics exhibit a nanocrystalline structure with an average crystallite size of ∼30 nm, high crystallinity, and minimal lattice strain (<0.5 %). Luminescence analysis from 4 K to 300 K reveals both intrinsic and europium-induced emissions. While intrinsic Ga₂O₃ emission exhibits thermal quenching above 100 K, Eu³⁺-related emissions, notably the 611 nm red emission, show thermal stability, retaining ∼90 % of their intensity at 300 K. Additionally, a novel low-temperature emission peak at 1.74 eV, potentially associated with electron beam-induced defects, was detected, meriting further exploration. These findings indicate that Ga₂O₃:Eu ceramics synthesized via EBAS hold promise for optoelectronic, radiation detection, and high-temperature applications, given their rapid production and enhanced thermal stability. © 2024 The Author(s) --//-- This is an open-access article Kuat K. Kumarbekov, Askhat B. Kakimov, Zhakyp T. Karipbayev, Murat T. Kassymzhanov, Mikhail G. Brik, Chong-geng Ma, Michał Piasecki, Yana Suchikova, Meldra Kemere, Marina Konuhova, Temperature-dependent luminescence of europium-doped Ga₂O₃ ceramics, Optical Materials: X, Volume 25, 2025, 100392, ISSN 2590-1478, https://doi.org/10.1016/j.omx.2024.100392.
This research was funded by Committee of Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant No. AP14972858). M.G.B. thanks the support from the Specialized Funding Program for the Gathering of 100 Elite Talents in Chongqing and the Overseas Talents Plan (Grant No. 2022 [60]) both offered by Chongqing Association for Science and Technology, the Polish NCN projects 2021/40/Q/ST5/ 00336, the Estonian Research Council grant (PRG 2031), and the Ministry of Science, Technological Development, and Innovation of the Republic of Serbia under contract 451-03-47/2023 01/200017. In addition, Marina Konuhova was supported by Latvian research project lzp-2023/1–0453 “Prediction of long-term stability of functional materials under extreme radiation conditions” and Latvian State Research Programme on Nr. VPP-IZM-CERN-2022/1-0001. Institute of Solid State Physics, University of Latvia, as the Center of Excellence, has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2. We acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. This research was carried out at P66 beamline at PETRA III. Beamtime was allocated for proposals I-20231138. We are thankful to the manager of P66 beamline at PETRA III Aleksei Kotlov for conducting synchrotron experiments.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Electron beam-assisted synthesis; Ga₂O₃:Eu; Luminescence; Сeramics